Investigating the reproducibility of maximal oxygen uptake responses to high-intensity interval training - Del Giudice, M.; Bonafiglia, J. T.; Islam, H.; Preobrazenski, H.; Amato, A.; Gurdlow, B. J. (Journal of Science and Medicine in Sport, 2020)
Objectives: To test the hypothesis that observed maximal oxygen uptake (VO2max) and time to fatigue (TTF) responses to two identical periods of standardized high-intensity interval training are reproducible. Design: Fourteen recreationally active and healthy young males completed two identical four-week periods of high-intensity interval training (4 × 4-min intervals at 90-95% maximum heart rate [HRmax] separated by 3-min periods of active recovery at 70-75% HRmax). Training periods were separated by a three-month washout period. Methods: VO2max and TTF were assessed via incremental tests with supramaximal verification before and after each training period. Pearson correlation coefficients (r), intraclass correlation coefficients (ICC), and within-subjects coefficients of variation (CV) were used to assess reproducibility of observed VO2max and TTF responses. Results: VO2max and TTF values before the second training period were not significantly higher than baseline values and there were no significant (p > 0.05) interaction effects (period 1: VO2max: +4.04 ± 2.29 mL/kg/min, TTF: +70.75 ± 35.87 s; period 2: VO2max: +2.83 ± 2.74 mL/kg/min, TTF: +83.46 ± 34.55 s). We found very weak-to-moderate correlations and poor reproducibility for observed VO2max (mL/kg/min: r = 0.40, ICC = 0.369, CV = 74.4) and TTF (r = 0.11. ICC = 0.048, CV = 45.6) responses to training periods 1 and 2. Conclusions: Our ANOVA results confirmed that the three-month washout period returned VO2max and TTF levels to baseline and prevented carryover effects. Contrary to our hypothesis, our results suggest that individual observed VO2max and TTF responses to identical training stimuli are not reproducible.